Validation of Academic Resilience Scales Adapted in a Collective Culture - Cui, Tianxue; Wang, Chuang; Xu, Jianzhong (Frontiers in Psychology, 2023)
The study aimed to adapt and validate two popular instruments on academic resilience in a collectivistic culture. One is a brief unidimensional scale (ARS_SCV), and another is a context-specific multidimensional scale (ARS_MCV). The participants were 569 high school students in China. Based on Messick’s validity framework, we provided evidence to support the construct validity of the newly developed scales. Results first indicated that both scales were reliable with high internal consistency and construct reliability. Then, the results of confirmatory factor analysis (CFAs) showed that ARS_SCV had a unidimensional factor structure and ARS_MCV had a four-factor structure. Multi-group CFAs then showed that both models were invariant across gender and socio-economic status (SES) levels. Results of correlations demonstrated that both scales significantly correlated with each other and with other external constructs (grit, academic self-efficacy, and learning engagement). The findings of this study contribute to the literature by proposing two instruments, which provide practitioners with options for specific assessments to measure academic resilience in a collectivist culture.